La ricerca empirica in pedagogia - Massimo Baldacci (Firenze University Press, 2010)
According to the author the pedagogical research has two convoys: the first epistemological (theoretical and historical), the other praxeology (experimental and empirical). Traveling together these two trains offer us the opportunity to see the face of critical pedagogy, or the reflexive dimension of doing research in education that translates better to the concept of action ricerca-azione. The most interesting aspect that emerges from this investigation is that the investigation is never separated from the 'action and results that follow are never objective and definitive.